Manzanar mosaic: essays and oral histories on America's first World War II Japanese American concentration camp - Hansen, Arthur A., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
Providing a new mosaic-style view of Manzanar's complex history through unedited interviews and published scholarship, Arthur A. Hansen presents a deep, longitudinal portrait of the politics and social formation of the Japanese American community before, during, and after World War II. To begin, Hansen presents two essays, the first centering on his work with Ronald Larson in the mid-1970s on the history of Doho, a Japanese and English dual-language newspaper, and the second an article with David Hacker on revisionist ethnic perspectives of the Manzanar "riot." A second section is composed of five oral history interviews of selected camp personalities-a female Nisei journalist; a male Nisei historical documentarian; a male Kibei Communist block manager; the Caucasian wife and comrade of the block manager; and the male Kibei who was the central figure in the Manzanar Riot/Revolt-that offer powerful insight into the controversial content of the two essays that precede them. Manzanar can be understood only by being considered within the much wider context of Japanese American community formation and contestation before, during, and after World War II. A varied collection of scholarly articles and interviews, Manzanar Mosaic engages diverse voices and considers multiple perspectives to illuminate aspects of the Japanese American community, the ethnic press, the Manzanar concentration camp, and the movement for redress and reparations.--Provided by publisher.
Doho: the Japanese American "Communist" press, 1937-1942 / Ronald C. Larson and Arthur A. Hansen -- The Manzanar "riot": an ethnic perspective / Arthur A. Hansen and David A. Hacker -- Oral histories: Sue Kunitomi Embrey, Togo Tanaka, Karl Yoneda, Elaine Black Yoneda, Harry Y. Ueno.
Keywords: Hansen, Arthur A. -- Interviews; Embrey, Sue Kunitomi -- Interviews; Yoneda, Karl G., 1906-1999 -- Interviews; Japanese Americans -- Forced removal and internment, 1942-1945; Yoneda, Elaine Black, 1906-1988 -- Interviews; World War, 1939-1945 -- Japanese Americans -- Personal narratives; Ueno, Harry Y. (Harry Yoshio), 1907-2004 -- Interviews; World War, 1939-1945 -- Japanese Americans -- Interviews; Tanaka, Togo, 1916-2009 -- Interviews; World War, 1939-1945 -- Evacuation of civilians -- United States; Manzanar War Relocation Center